Pengaruh Kredit Investasi dan Kredit Modal Kerja Terhadap Kesejahteraan Masyarakat Kabupaten/Kota di Jawa Timur - Agus Sumanto (Universitas Negeri Malang, 2016)
The development of investment credit and working capital credit in the regencies/ municipalities in East Java so rapidly, with an average of over 20% per year from 2003 to 2012. The benefit of the credit on the increase in output, employment and the social welfare need to be evaluated. This study finding that the benefit of the investment credit for the social welfare is negative, but the usefulness of working capital credit is positive. After the analysis is done, the cause is the shift of investment from labor-intensive to capital-intensive investments, where in capital intensive investment, labor absorption is low. As a further consequence, social welfare decreased despite increase in investment credit occur. It is advisable to make an investment credit policies that easy accessable to micro, small and cooperatives that can absorb more labor than of medium and large enterprises. Keywords: investment credit, working capital credit, output, labour absorption